Gender and socioeconomic inequalities in changes in a Mediterranean lifestyle among elderly Italians: Marialaura Bonaccio. (25th October 2022) - Bonaccio, M; Gianfagna, F; Stival, C; Amerio, A; Bosetti, C; Cavalieri d'Oro, L; Odone, A; Zucchi, A; Gallus, S; Iacoviello, L
Abstract: The COVID-19 pandemic and the adoption of restrictive measurements to control the SARS-CoV-2 spread disrupted general population lifestyles including dietary behaviours. However, there is poor knowledge on potential socioeconomic and gender disparities in dietary changes. We conducted a telephone-based survey during fall 2020 on a sample of 4, 400 participants representative of the population aged 65-99 years living in Lombardy, Italy. Changes in a Mediterranean lifestyle were assessed retrospectively by asking participants to report modifications in the consumption of nine food groups and five diet-related behaviours (e.g., consumption of organic and local foods) compared to the previous year (2019). We then computed a Mediterranean COVID-19 Pandemic Score (MedCovid-19 Score), reflecting changes during pandemic, ranging from -14 to 14, with increasing values indicating improvements in line with a Mediterranean lifestyle. Overall, 18.3% of the study participants worsened their Mediterranean lifestyle (MedCovid-19 Score <0), 35.1% remained stable (MedCovid-19 Score = 0), while 46.6% reported improvements (MedCovid-19 Score ≥1). Predictors of favourable changes toward a Mediterranean lifestyle were educational level (OR = 1.52; 95% CI 1.19-1.95 for postgraduate vs lower education), wealth (OR = 1.52; 1.14-2.02 for high vs low wealth), and skilled manual occupations (OR = 1.57; 1.28-1.92 vs white collars). Women were more likely than men to move away from a Mediterranean lifestyle (OR = 1.86; 1.58-2.21). In conclusion, improvements in line with a Mediterranean lifestyle prevailed in almost half of a large sample of elderly Italians surveyed during the COVID-19 pandemic. However, changes towards a Mediterranean lifestyle were disproportionately distributed across gender and socioeconomic strata. These findings were similar to those from the general population of the Moli-sani study, where it was observed that healthful dietary changes were associated greater wealth.